The COMPARE Database: A Public Resource for Allergen Identification, Adapted for Continuous Improvement - van Ree, Ronald; Sapiter Ballerda, Dexter; Berin, M. Cecilia; Beuf, Laurent; Chang, Alexander; Gadermaier, Gabriele; Guevera, Paul A.; Hoffmann-Sommergruber, Karin; Islamovic, Emir; Koski, Liisa; Kough, John; Ladics, Gregory S.; et al. (Frontiers in Allergy, 2021)
Motivation: The availability of databases identifying allergenic proteins via a transparent and consensus-based scientific approach is of prime importance to support the safety review of genetically-modified foods and feeds, and public safety in general. Over recent years, screening for potential new allergens sequences has become more complex due to the exponential increase of genomic sequence information. To address these challenges, an international collaborative scientific group coordinated by the Health and Environmental Sciences Institute (HESI), was tasked to develop a contemporary, adaptable, high-throughput process to build the COMprehensive Protein Allergen REsource (COMPARE) database, a publicly accessible allergen sequence data resource along with bioinformatics analytical tools following guidelines of FAO/WHO and CODEX Alimentarius Commission. Results: The COMPARE process is novel in that it involves the identification of candidate sequences via automated keyword-based sorting algorithm and manual curation of the annotated sequence entries retrieved from public protein sequence databases on a yearly basis; its process is meant for continuous improvement, with updates being transparently documented with each version; as a complementary approach, a yearly key-word based search of literature databases is added to identify new allergen sequences that were not (yet) submitted to protein databases; in addition, comments from the independent peer-review panel are posted on the website to increase transparency of decision making; finally, sequence comparison capabilities associated with the COMPARE database was developed to evaluate the potential allergenicity of proteins, based on internationally recognized guidelines, FAO/WHO and CODEX Alimentarius Commission Availability and Implementation: COMPARE was first released in January 2017 (COMPARE 2017) and updated annually since then. It is publicly available at: http://www.comparedatabase.org. Bioinformatics analytical tools (COMPASS) associated with the COMPARE allergen database is publicly available directly from the database page, or via: https://comparefasta.foodrisk.org/.